Inventory Information System Design at PT. Arsen Kusuma Indonesia Jakarta - Dahlia Sarkawi; Dani Ramdani; Anggi Oktaviani; Deny Novianti (Jurnal Riset Informatika, 2020)
An inventory Information System is an Information System that provides information from several processes including procurement of goods, warehousing, and reporting. Therefore it is necessary to create an Inventory Information System application to improve the company's performance process which originally became computerized which will result in more detailed reports. The creation of this application is done using data collection, system planning, system analysis, system design, and database. Application program creation was developed with PHP and Waterfall model as well as tested using black-box testing. And it is expected that the manufacture of this application can facilitate the company in processing the inventory of goods, then in this research was made Designing Inventory Information System At PT. Arsen Kusuma Indonesia Jakarta.